Neurologic Manifestation in Children with Coronavirus Disease 2019 at Prof. Dr. I.G.N.G Ngoerah Tertiary Hospital - Husin, Michelle; Mahalini, Dewi Sutriani; Suwarba, I Gusti Ngurah Made; Purniti, Ni Putu Siadi; Subanada, Ida Bagus (Open Access Macedonian Journal of Medical Sciences, 2023)
AIM: The objective of the study is to describe neurologic manifestation in children with coronavirus disease-2019 (COVID-19) at Prof. Dr. I.G.N.G Ngoerah Hospital. METHODS: This was a retrospective descriptive study using the medical record with a total sampling of children with confirmed COVID-19 that manifests neurologic symptoms. Exclusion criteria were pre-existing neurologic comorbidities and incomplete medical records. RESULTS: From March 2020 to December 2021, from 308 children with confirmed cases of COVID-19, 106 had neurologic symptoms, 17 were excluded (16 pre-existing comorbidities, and 1 incomplete medical record), and total samples were 89 (28.8%) from inpatient and outpatient. Most children were male (57.3%) with a median age of 13 years. Most symptoms found were anosmia (73%), followed by a decrease in consciousness (19.1%) and seizure (10.1%). Children with anosmia median age were 14 years. There were 84 (94.3%) children with specific neurological symptoms (encephalopathy, seizures, and anosmia) and 5 (5.7%) with non-specific neurological symptoms (headache). CONCLUSION: There were 28.8% confirmed cases of COVID-19 with a neurologic manifestation, and most symptoms found were anosmia (73%).